Cost-effectiveness of minimally invasive sacroiliac joint fusion - Cher, Daniel J (Clinicoecon Outcomes Res, 2015)
BACKGROUND: Sacroiliac joint (SIJ) disorders are common in patients with chronic lower back pain. Minimally invasive surgical options have been shown to be effective for the treatment of chronic SIJ dysfunction. OBJECTIVE: To determine the cost-effectiveness of minimally invasive SIJ fusion. METHODS: Data from two prospective, multicenter, clinical trials were used to inform a Markov process cost-utility model to evaluate cumulative 5-year health quality and costs after minimally invasive SIJ fusion using triangular titanium implants or non-surgical treatment. The analysis was performed from a third-party perspective. The model specifically incorporated variation in resource utilization observed in the randomized trial. Multiple one-way and probabilistic sensitivity analyses were performed. RESULTS: SIJ fusion was associated with a gain of approximately 0.74 quality-adjusted life years (QALYs) at a cost of US$13,313 per QALY gained. In multiple one-way sensitivity analyses all scenarios resulted in an incremental cost-effectiveness ratio (ICER) <$26,000/QALY. Probabilistic analyses showed a high degree of certainty that the maximum ICER for SIJ fusion was less than commonly selected thresholds for acceptability (mean ICER =$13,687, 95% confidence interval $5,162–$28,085). SIJ fusion provided potential cost savings per QALY gained compared to non-surgical treatment after a treatment horizon of greater than 13 years. CONCLUSION: Compared to traditional non-surgical treatments, SIJ fusion is a cost-effective, and, in the long term, cost-saving strategy for the treatment of SIJ dysfunction due to degenerative sacroiliitis or SIJ disruption.